Mapping of Muslims’ Understandings on Gender Issues in Islam at Six Universities in Yogyakarta, Indonesia - Alimatul Qibtiyah (Al-Jami'ah Research Centre, 2018)
There is considerable disagreement among Muslims in how Islam says about many gender issues. One factor that influences the ways in which people understand gender issues in Islam and deal with the associated controversy is the approach they take when reading and interpreting Islamic texts. Some research has been done on the variety of thoughts on Islamic studies, but mapping thoughts comprehensively on gender issues not yet explored. This paper maps the Muslims’ understanding of six contentious gender issues in Islam into three approaches: textualist/conservative, semi-textualist/moderate, and contextualist/progressive approaches. I document the diversity of thought among feminist and non-feminist Muslim intellectuals on gender issues (in the light of their faith) using documentation and in-depth interview techniques. 25 respondents (male and female) from six universities in Yogyakarta were selected in this research. Textualist/conservative and contextualist/progressive scholars show the most strongly contrasting views on gender issues in Islam. Semi-textualist/moderates present their views relatively flexibly: sometimes their views match those of the textualist/conservatives: sometimes they align closely with the contextualist/progressives. Based on their views and the arguments they present, semi-textualist/moderates’ and contextualist/progressives’ views seem close to the stance adopted by many Islamic Feminist. [Masih terdapat perbedaan pendapat antar umat Islam memahami isu gender. Salah satu faktor berpengaruh dalam pemahaman isu gender pada Islam adalah hal kontroversial dalam pendekatan pembacaan dan penafsiran teks agama. Beberapa penelitian telah mengkaji keragaman dalam pemikiran keislaman, namun pemetaan pemikiran secara komprehensif mengenai isu gender belum banyak. Tulisan ini memetakan pemahaman para feminis tentang enam isu gender dalam Islam di tiga kelompok (1) tekstual – konservatif, (2) semi tektual – moderat, dan (3) kontekstual – progresif. Artikel ini mengambil lapangan di 6 universitas Yogyakarta dengan wawancara lebih dari 25 informan laki – laki dan perempuan baik feminis dan non feminis. Kelompok tektualis dan kelompok kontekstual merupakan dua kelompok yang saling bertentangan dan kelompok semi tekstual lebih pada fleksibel. Terkadang pandangan ke tiga kelompok bergeser saling mendekat dan menjauh. Berdasarkan pandangan dan argumentasi ke tiga kelompok tersebut, semi tektual dan kontekstual menggambarkan kecondongan lebih banyak pada adopsi feminis muslim].